2007
DOI: 10.1017/s0033291707009956
|View full text |Cite
|
Sign up to set email alerts
|

The temporal dynamics of relationships between cannabis, psychosis and depression among young adults with psychotic disorders: findings from a 10-month prospective study

Abstract: Continued cannabis use by persons with schizophrenia predicts a small increase in psychotic symptom severity but not vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 27 publications
6
65
0
Order By: Relevance
“…In spite of the strictures of Macleod (2007), previous research is generally in line with the report recently published by Degenhardt et al (2007), which provides further evidence to challenge the hypothesis that psychotic patients take cannabis to ameliorate their symptoms. For example, in both the population-based study of Henquet et al (2005) and in the large Dunedin birth cohort sample (Arseneault et al 2002), psychotic symptoms failed to predict later cannabis use.…”
Section: Commentsupporting
confidence: 82%
“…In spite of the strictures of Macleod (2007), previous research is generally in line with the report recently published by Degenhardt et al (2007), which provides further evidence to challenge the hypothesis that psychotic patients take cannabis to ameliorate their symptoms. For example, in both the population-based study of Henquet et al (2005) and in the large Dunedin birth cohort sample (Arseneault et al 2002), psychotic symptoms failed to predict later cannabis use.…”
Section: Commentsupporting
confidence: 82%
“…This is consistent with other follow-up studies that compared positive symptom levels between continued users, discontinued users and non-users of cannabis 22-25 and a report from a longitudinal population-based sample suggesting that continuation of cannabis use predicted subsequent persistence of psychotic symptoms 80 . Other studies have reported a temporal association between changes in cannabis use and subsequent changes in psychotic symptom severity, both in the short 81 and long-term 14 . Evidence that cannabis use has a particularly harmful effect on different outcome measures of psychosis (relapse, psychotic symptoms) when use is continued compared to when one stops using is intuitive and consistent with effects of cannabis use on cognition 79 .…”
Section: Discussionmentioning
confidence: 92%
“…Degenhardt L, Tennant C, Gilmour S, Schofield D, Nash L, Hall W, McKay D (2007). The temporal dynamics of relationships between cannabis, psychosis and depression among young adults with psychotic disorders : findings from a 10-month prospective study.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…The argument of psychiatrists and other mental health-care professionals against giving such advice is that since the effect of cannabis on psychosis is nothing or negligible, psychiatry must not portray itself as a ' killjoy' profession, because this could lead to fewer mentally ill patients trusting psychiatrists to help them. On the other hand, Macleod (2007), in his excellent commentary on Degenhardt et al (2007), considers that trying to prevent or reduce cannabis use amongst the mentally ill patients is justifiable, even when one considers its apparently small effect on psychosis. He supports this opinion by underlining that cannabis is not only deleterious on psychosis, but it is also a contributing factor to physical health problems.…”
mentioning
confidence: 99%